Effect of conjugated polymer poly (9, 9-dioctylfluorene) (PFO) molecular weight change on the single chains, aggregation and β phase. (26th October 2016) - Li, Tao; Liu, Bin; Zhang, Hao; Ren, Jiaxuan; Bai, Zeming; Li, Xiaona; Ma, Tengning; Lu, Dan
Abstract: In the work, the effect of PFO molecular weight change on the single chains, aggregation and β phase in the solution was investigated. Some regularity of the chain size and shape with the molecular weight change in the dynamics process were revealed and related mechanism was explored. It was found that the β phase content of high molecular weight was higher than that of low molecular weight in the range of 47, 000 to 145, 000 g/mol. The main reason was the intrachain interaction which led to the fold of chain itself. When PFO molecular weight was higher, the β phase can be easier formed as the intrachain interaction was stronger to fold itself to overcome the steric repulsion. Besides, single chain with lower molecular weight was more rigid than that of higher molecular weight in pure chloroform, but formed aggregation with low molecular weight was bigger and denser from the results of SLS/DLS, fractal dimension ( d f ) and TEM. It was inferred that the reason for this phenomenon was the fold of chain itself and the β phase. For chains with high molecular weight, they were comparatively long and flexible; it was easy for them to be folded to enhance the steric hindrance between different chains, so they were loosely packed. The ordered β phase occupied less volume compared to the α phase as the β conformation was more planar and packed tightly, and the proportion of β phase was more in aggregation of high molecular weight, so the aggregation size of high molecular weight was smaller than that of low molecular weight. This study is significant to control the β phase content in solution so as to increase the charge carrier mobility of the photoelectric films and the devices efficiency. Graphical abstract: Highlights: The relationship between molecular weight and PFO β phase was revealed. The β phase was formed by the fold of chain itself. This study is significant to control β phase content in solution.